NLP Models for Mental Health-Related Text Analysis in Brazilian University Reddit Communities - Rocha, Tiago C. B.; Dallagnol, Leonardo P.; Marques, Maicon C.; Silva, Camila O.; Vilaça, Júlia O.; Ponciano, Jean R. (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD), 2026)
Online communities have become important spaces for mental health discussions among university students, generating large volumes of text that are difficult to analyze manually at scale. This work investigates automated methods for analyzing emotional and relational aspects of mental health-related text in three Brazilian university Reddit communities. We employed NLP models to evaluate two dimensions: the emotional tone expressed in the text and the presence or absence of supportive social interaction. The results indicate that automated methods are suitable for scalable identification of social support behaviors, while emotional tone analysis requires greater caution and is best applied to clearly polarized expressions rather than fine-grained neutral distinctions.